A gestational dose of vitamin D per day keeps the MS doctor away. (3rd January 2017) - Marrie, Ruth Ann; Daumer, Martin
Abstract : Interest in identifying the cause of multiple sclerosis (MS) remains intense. Two nested case-control studies showed that in young, predominantly white adults in whom samples were collected before clinical disease onset, higher serum levels of 25(OH)D were associated with a reduced risk of developing MS. 1, 2 In the Nurses' Health Study cohorts, higher dietary intake of vitamin D was associated with a lower risk of developing MS among American nurses; supplemental intake of more than 400 IU daily was associated with a 40% reduced risk. A more recent mendelian randomization study, which included 14, 498 MS cases and 24, 091 healthy controls with European ancestry, showed that alleles related to lower vitamin D levels were associated with increased MS risk. 2, 3 This study design increases the confidence that the preceding observations reflect a causal association rather than confounding. However, the time period when vitamin D exposure is relevant to reducing MS risk remains uncertain, including whether early-life exposure to vitamin D influences MS risk. 2, 4